2021
DOI: 10.3390/app11072959
|View full text |Cite
|
Sign up to set email alerts
|

Using Mg/Ca Ratios from the Limpet Patella depressa Pennant, 1777 Measured by Laser-Induced Breakdown Spectroscopy (LIBS) to Reconstruct Paleoclimate

Abstract: Measurement of the elemental composition of shells is increasingly emerging as an avenue for obtaining high-resolution insights into paleoclimate and past seasonality. Several studies have shown significant correlations between Mg/Ca ratios measured on shell carbonate and the sea surface temperature (SST) within which this carbonate was precipitated. However, other investigations have reported large variability in this relationship between species. Therefore, further studies, including taxa previously not cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 91 publications
0
12
0
Order By: Relevance
“…With the great advances of component technology and artificial intelligence, cost-effective miniaturized PS-LIBS are becoming increasingly popular. They have been implemented in a wide set of sectors applications, such as product and processes monitoring in Industry 4.0, environmental monitoring, medical diagnosis, biochemical-agent detection, and archaeological samples, just to mention a few [ 91 , 92 , 93 ]. Thus, PS-LIBS shows a great growth potential both in the scientific field and in various industries.…”
Section: Ten Significant Cases Of Photonic Sensorsmentioning
confidence: 99%
“…With the great advances of component technology and artificial intelligence, cost-effective miniaturized PS-LIBS are becoming increasingly popular. They have been implemented in a wide set of sectors applications, such as product and processes monitoring in Industry 4.0, environmental monitoring, medical diagnosis, biochemical-agent detection, and archaeological samples, just to mention a few [ 91 , 92 , 93 ]. Thus, PS-LIBS shows a great growth potential both in the scientific field and in various industries.…”
Section: Ten Significant Cases Of Photonic Sensorsmentioning
confidence: 99%
“…LIBS offers multiple advantages over other analytical techniques including versatility, no contact requirements, multi-elemental analysis, it being practically non-destructive, and a reduction in, or lack of, sample preparation [34]. Measuring solid samples, such as mollusk shells, with the commonly used techniques for this purpose (ICP-OES or ICP-MS) requires micro-milled sampling procedures and subsequent acid digestion, which can be highly time-consuming compared to LIBS procedure which offers a number of benefits in the context of more limited sample preparation requirements, lower costs, and an increased rapidity in measurement and accumulation of data from multiple individuals from a given context [35][36][37]. Laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS) is a highly accepted and widely used technique for the analysis of major, minor and trace elements, as well as isotope-ratio determination [38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, LIBS offers more versatility, improved speed, ease of operation, affordability and portability [44]. Previous work has demonstrated that Mg/Ca ratios obtained along the growth axis of limpets using LIBS showed very well-defined seasonal cycles that correctly reflected the annual variations in SST [36,37,[45][46][47]. However, one of the main issues with the LIBS technique is that the spectral line intensities from a given element are strongly dependent on the physical and chemical properties of the sample (the so-called matrix effect) [37].…”
Section: Introductionmentioning
confidence: 99%
“…A. García-Escárzaga et al [17] propose a novel methodology for paleoclimate applications in northern Spain, based on the measurement of Mg/Ca ratios using Laser-Induced Breakdown Spectroscopy (LIBS) in live-collected samples for limpet Patella depressa26 Pennant, 1777. The results showed a significant correlation between Mg/Ca ratio series and both δ18O profiles and SST, highlighting the palaeoenvironmental and archaeological potential of LIBS analyses on this mollusc species that is frequently found in archaeological contexts in the western Europe.…”
mentioning
confidence: 99%
“…Finally, the biogeochemical study of molluscs has been proved as a relevant approach for palaeoclimate reconstructions; refs. [17,18] show the potential of palaeolimnology to detect human-induced eutrophication.…”
mentioning
confidence: 99%